Diferenciação morfométrica da concha de Anodontites trapesialis (Lamarck, 1819) (Mollusca-Bivalvia) em diferentes bacias hidrográficas brasileiras - Marques, Rafael Cavalheiro (Universidade Federal de São Carlos, 2021)
Considering the relevance of Anodontites trapesialis, a freshwater bivalve of the Mycetopodidae family that has differences in shell shape throughout its wide distribution, this study analyzed and morphometrically compared individuals of A. trapesialis from different watersheds, seeking to select shell characteristics that could help in the identification of the species, and looking for relevant morphological and biogeographic information. The collections used were: MZUSP, UFMT, MCN - FZB and CIB (UFSCar). From a total of 118 analyzed individuals, 35 belonged to Paraguay river basin, 32 to Paraná, 18 to Uruguay, 18 to South Atlantic and 15 to Amazon river basin. Photographic records were taken from the internal face of each specimen shell, where the landmarks were localized (10 in total). With the TPSDIG software, landmarks were digitized, and x and y coordinates of each landmark were obtained. With the MorphoJ software, these coordinates were overlaid using GPA (General Procrustes Analysis) separating size and shape components and generating a matrix of the procrustes coordinates, that were used later in statistical analysis. The statistical analysis made were Procrustes Anova, Principal Components Analysis (PCA), Canonical Variate Analysis (CVA, maximum shell shape differentiation), Discriminant Analysis with cross validation and Mahalanobis Distance. The Procrustes Anova indicated significant differences between populations according to latitude (F=4,87 p<0,0001), while the PCA pointed that the axis that best explain the difference between shell shapes were 1 (40,918% of variation) e 2 (16,588%). The CVA resulted in 2 main axes: the 1st axis (shape) explained 51,356% of the variation - the analysis showed significant difference among Uruguay river and Paraguay river basins, and slight difference showing an overlay between other river basin groups. The Discriminant Analysis showed high percentages of identification, confirming the CVA (higher percentages show groups with higher distance, resulting in 100% when comparing Uruguay and Paraguay river basins), and showing that the shells from Paraguay and Amazon River basins are taller, while the ones from Paraná, Uruguay and South Atlantic are usually rhomboid. When analysing Mahalanobis Distance, the biggest difference is found between the populations from Amazon River basins and South Atlantic watershed, matching the higher geographic distance. The regression analysis allying the centroid size and the Regression Score pointed that a fraction of the shape variation is influenced by the size of the shell. Finally, this study led to the conclusion that there are differences between populations from varied basins, such as greater (like those from Paraguay river basin) or shorter heights (such as the ones from Paraná river basin), with similar shapes (such as South Atlantic and Uruguayan shells) or contrasting shapes (alike those from Uruguay and Paraguay), all that taking into account that a fraction of all variation is related to size and other fractions are related to environmental variables.
Morphometric differentiation of the Anodontites trapesialis shell (Lamarck, 1819) (Mollusca-Bivalvia) in different Brazilian hydrographic basins
Keywords: Unionoida; Mycetopodidae; Morfometria geométrica; Morfologia; Taxonomia; Biogeografia; Geometric morphometric; Morphology; Biogeography; Taxonomy; CIENCIAS BIOLOGICAS::MORFOLOGIA